Development of mechanism for formation and activation of territorial image potential - Olha Zinchenko (Tehnologìčnij Audit ta Rezervi Virobnictva, 2018)
The object of research is the mechanism of formation and activation of the potential of the regional image. In the practice of regional management, a certain algorithm for creating an image is used, but the problem is the lack of a single tool for assessing and attracting the potential of the territory to create its attractive image. To overcome this problem, the author developed a mechanism for forming and activating the potential of a regional image. This mechanism envisages the attraction to the image-making system of the territory of its entire resource potential, a very broad toolkit not only of administrative science, but also of sociology, psychology, economic analysis, and marketing.